Design and development of C3 protocol for performance measurement of wireless sensor network - S. Patil, Kasturi (International Journal of Engineering and Technology, 2018)
In twenty-first century, technology changes tremendously. A wireless sensor network is bunch of sundry sensor nodes where, nodes are distributed arbitrarily. Sensor consumes most of its energy in data transmission and reception. System ascertained different amended protocols for performance quantification of WSN. Sensing node sense environment but doesnâ€™t transmit or receive the data. Slumber nodes neither sense environment nor transmit or receive data. Proposed system validate the analytical models utilizing extensive simulations incorporating experimental results on the substratum of different parameter here performance is checked. A protocol for communication and connectivity in Wireless Sensor Network is proposed. This ascertains coverage, connectivity and energy-efficient communication. It contains steps such as: Declaration of deployment area, cull of nodes, connectivity of nodes, and communication between all nodes.Â Â